Protector and friend: Turning points and discursive constructions of the stepparent role. Issue 3 (19th January 2022) - Oliver‐Blackburn, Bailey M.; Braithwaite, Dawn O.; Waldron, Vincent R.; Hall, Robert; Hackenburg, Lucas; Worman, Braedon G.
Abstract: Objective: To understand turning points (TPs) in the development of positive stepparent–stepchild communication and relationships. Background: Scholars stress the importance of communication in co‐constructing healthy stepparent–stepchild relationships. The researchers focused on positive stepparenting via understanding transformational turning point (TP) events across time. Research questions explored how stepparents with an overall positive relationship with a stepchild characterize TPs and the discursive constructions of the stepparent role. Method: The team analyzed 877 pages of data from 37 in‐depth interviews with stepparents who described self‐identified TP events, reflected in visual graphs of 279 TPs. Results: Data were coded into 11 TP types, focused on structural and role changes for stepparents, co‐constructed over time. The top three TP types were changes in household composition, communicating support through offering protection and being present/available, and role change, most frequently by functioning as a parent versus friend. All the TPs highlight discursive work to forge positive stepparenting roles. Conclusions: The findings extend earlier studies of stepchildren's experiences and communication practices that ground resilience to manage relational resources through investments of quality time and enactment of social support. Implications: Applications suggest support for stepparents to have quality interactions with stepchildren and training to develop healthy communication practices and facilitate resilience.